Dendritic cells control T cell tonic signaling required for responsiveness to foreign antigen - Hochweller, Kristin (National Academy of Sciences, 2010)
Dendritic cells (DCs) are key components of the adaptive immune system contributing to initiation and regulation of T cell responses. T cells continuously scan DCs in lymphoid organs for the presence of foreign antigen. However, little is known about the functional consequences of these frequent T cell–DC interactions without cognate antigen. Here we demonstrate that these contacts in the absence of foreign antigen serve an important function, namely, induction of a basal activation level in T cells required for responsiveness to subsequent encounters with foreign antigens. This basal activation is provided by self-recognition of MHC molecules on DCs. Following DC depletion in mice, T cells became impaired in TCR signaling and immune synapse formation, and consequently were hyporesponsive to antigen. This process was reversible, as T cells quickly recovered when the number of DCs returned to a normal level. The extent of T cell reactivity correlated with the degree of DC depletion in lymphoid organs, suggesting that a full DC compartment guarantees optimal T cell responsiveness. These findings indicate that DCs are specialized cells that not only present foreign antigen, but also promote a “tonic” state in T cells for antigen responsiveness.